Content Analysis of High School History Textbook From Hans Kohn's Nationalism Perspective - Wardhana, Ivan Prapanca; Samsiyah, Siti (Sebelas Maret University (UNS), 2019)
This study aims to analyze nationalism in history textbooks at the Senior High School level. History textbooks contain nationalism material that is closely related to Hans Kohn's theory of nationalism. The nationalism is shown as the highest form of individual loyalty submitted to the state in the history textbook of Indonesia volume 2 for class XI high school. The method used to determine the nationalism contained in textbooks using the nationalism approach developed by Hans Kohn. The results showed that the influence of nationalism was very strong on the writing of the sample textbook history lessons studied. This influence can be seen from the inculcation of the attitude of nationalism as a form of government obligation in an effort to shape the character and personality of the nation. In addition, this was done to strengthen nationalism through education.